Assessing fundamental motor skills proficiency in school-based sports physical education programs: implications for talent development - Makaruk, H.; Webster, E. K.; Porter, J.; Makaruk, B.; Bodasinska, A.; Zielinski, J.; Tomaszewski, P.; Nogal, M.; Starzak, M.; Sliwa, M.; Banas, M.; Biegajlo, M.; et al. (Frontiers in Sports and Active Living, 2025)
Introduction: Fundamental motor skills (FMS) are essential for fostering physical literacy, supporting talent development, and promoting public health in school-aged populations. This study aimed to evaluate FMS proficiency among students in school-based sports physical education (PE) programs, which offer sport-specific training, and compare it to students in traditional PE programs. A secondary aim was to examine whether these programs promote early specialization or early diversification in youth sport development.